Lítio e parâmetros orbitais em sistemas binários com componentes evoluídas - Costa, João da Mata (2001)
One of the best established properties of the single late type evolved stars is that their rotational velocity and lithium content decrease with effective temperature and age. Nevertheless, the root cause of this property, as well as the link between rotation and lithium abundance and, in particular, the effects of binarity on rotation and lithium content in binary systems with evolved component, are not yet completely established. How does the gravitational tides, in binary systems, affects rotational evolution and lithium dilution? Trying to answer these questions, we have carried out an observational survey, in the lithium region centered at the lithium I line A6707.81A, for a large sample of about 100 binary systems with evolved component along the spectral range F, G and K, with the CES spectrometer mounted at the CAT 1.44 m Telescope of the ESO, La Silla, Chile. By combining the abundances of lithium issued from these observations with rotational velocity and orbital parameters, we have found a number of important results. First of all, we confirm that in this class of binary systems rotation is effectively affected by tidal effects. Binary systems with orbital period lower than about 100 days and circular or nearly circular orbits, present rotational velocity enhanced in relation to the single giant stars and to the binary systems with an orbital period larger than 100 days. This is clearly the result of the synchonization between the rotational and orbital motions due to tidal effects. In addition, we have found that lithium abundances in binary systems with giant components present the same gradual decreasing with effective temperature, observed in the single giants of same luminosity class and spectral types. We have found no lithium-rich binary systems, in contrast with single giants. A remarkable result from the present study is the one showing that synchronized binary systems with giant component retains more of their original lithium than the unsynchronized systems. In fact, we have found a possible "inhibited zone", in which synchronized binary systems with giant component having lithium abundance lower than a threshold level should be unusual. Finally, the present study also shows that the binary systems with giant component presenting the highest lithium contents are those with the highest rotation rates